A quest for a structural tribal formation of knowledge - Isenyo Solomon Ogaba (International Journal of Humanities and Innovation (IJHI), 2021)
The cognitive view of life and the total environment that an individual holds or which is characteristic of a society's members is frequently referred to as Weltanschauung, or world view. It is thus the life scene as people look out upon it. Worldviews grow with cultures. Generations of anonymous human beings contribute to the unending quest to make the unknown knowable, to transform meaningless bafflement into meaningful understanding. There are individuals in every society, no doubt who are thinkers and systematizes, the idealists who crystallize the myths, shape the ceremonies, express the concepts in art – symbolic creators. However, even they must work within the cultural framework. The tribal people are known to have a strong worldview. The way they perform, perceive and explain the natural and supernatural phenomenon, social and cultural events, relationships within themselves and outside, and diseases and grievances reflect a manifestation of their concept of different aspects of life, often referred to as ‘worldview’. However, tribal knowledge has often been criticized as unscientific or incoherent with science, and therefore, lacks philosophical explanation. The present study, therefore, aims to investigate tribal worldviews. This paper acknowledges that since each tribal group is unique and different from one another, it is not possible to discuss their various worldviews in this paper. However, this paper attempt to x-ray basic assumption that cut across most tribal worldviews.